Synthesis, Characterization and Antioxidants Silver Nanoparticles Leaves of Prosopis Juliflora and Mentha Piperita - Abdalrahem Bin Selim, Elham; M. Ismail, Rokhsana; Ruban, Suhair (Al-Nahrain Journal of Science, 2025)
It is known that the green method is one of the environmentally friendly methods which attracted great attention by many researchers. So, our study focusing on the synthesis and characterization of silver nanoparticles (AgNPs) from stock solutions of silver nitrate, AgNO3 (0.001 M) of two aqueous solutions of extracted leaves of Prosopis Juliflora and Mentha Piperita. The structure, geometry, and sizes of the synthesised silver nanoparticles were identified by Ultraviolet-Visible (UV-Vis), Fourier transform infrared (FTIR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and electron dispersive X-ray (EDX) analysis. The formation of AgNPs was confirmed by the presence of a strong characteristic peak in the UV-Vis spectrum at around 425 nm. The FTIR showed the important functional groups. The synthesized silver nanoparticles have spherical shapes, individually ranging from 6.67-13.9 and 6.10-15.5 nm for Prosopis Juliflora (P. Juliflora) and Mentha Piperita (Mentha P.) extracts. The antioxidant activity of the obtained AgNPs was tested using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay. It was found that they showed very powerful potent antioxidants.